2014
DOI: 10.1073/pnas.1413965111
|View full text |Cite
|
Sign up to set email alerts
|

Meal frequency and timing in health and disease

Abstract: Although major research efforts have focused on how specific components of foodstuffs affect health, relatively little is known about a more fundamental aspect of diet, the frequency and circadian timing of meals, and potential benefits of intermittent periods with no or very low energy intakes. The most common eating pattern in modern societies, three meals plus snacks every day, is abnormal from an evolutionary perspective. Emerging findings from studies of animal models and human subjects suggest that inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
379
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 463 publications
(399 citation statements)
references
References 85 publications
7
379
0
13
Order By: Relevance
“…In line with previous publications [26, 27, 28, 29, 69] it can be hypothesized that the health‐ and life‐span extending effects are not necessarily derived from the energy reduction only, but that intermittent exposure to challenges might have an additional health‐promoting effect. Apart from exposure to alternating energy availability in this study the gastrointestinal tract as well as metabolic organs like the liver, were challenged to handle variations in carbohydrate and fat content.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In line with previous publications [26, 27, 28, 29, 69] it can be hypothesized that the health‐ and life‐span extending effects are not necessarily derived from the energy reduction only, but that intermittent exposure to challenges might have an additional health‐promoting effect. Apart from exposure to alternating energy availability in this study the gastrointestinal tract as well as metabolic organs like the liver, were challenged to handle variations in carbohydrate and fat content.…”
Section: Discussionsupporting
confidence: 80%
“…Importantly, increasing evidence points out that the beneficial health effects of (intermittent) CR are not solely caused by reduced body weight 24, 25. Timing and limitation of meal frequency affect the circadian rhythm and might induce a repetitive challenge that most likely will contribute to the health promoting effects 26, 27, 28, 29. We recently reported that an intermittent energy restriction (INT) diet maintains metabolic health and reverses the adverse effects of the moderate‐fat (MF) diet, when provided for 10 months to 9‐week‐old male C57BL/6J mice 30.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these findings have implications for glucose regulation and may help explain why shift work is a risk factor for type 2 diabetes. Our observations underscore results from recent studies in humans and animals that suggest that it is not merely what we eat, but also when we eat, that has important health consequences, including for glucose metabolism (59). Our findings may also help the development of behavioral and circadian strategies (e.g., timing of eating) that could improve glycemic control in dayactive people and night workers.…”
Section: Discussionsupporting
confidence: 76%
“…Due to similarities in mechanism, many of the side effects are common with varying magnitudes of severity. It appears that the SGAs, amisulpride, clozapine, olanzapine and risperidone demonstrate improvements in overall, positive and negative symptoms [4,9] relative to FGAs. Despite a favorable safety profile [10], it is shown that SGAs, particularly olanzapine and clozapine, are also associated with the most significant weight gain.…”
Section: Abstract: Fasting; Antipsychoticsmentioning
confidence: 96%
“…This is pertinent considering it has been shown that lifestyle modifications are possible with people experiencing severe mental illness [11]. To prevent the weight gain associated with antipsychotic medications, intermittent fasting through the use of circadian based feeding/fasting windows may be useful in reducing the consequences and severity of insulin resistance [9].…”
Section: Abstract: Fasting; Antipsychoticsmentioning
confidence: 99%